Homeschooling in the United States the Past, the Present, and the Future (International Journal of Innovative Research in Engineering & Management, 2021)
This article looks at the impact of right wing and left-wing political radicalism, feminist, suburban  sprawl, and publicly education institutionalization and  reformation on the homeschool phenomenon in the United  States. It then goes on to clarify how the movement, which  included components from both the left and right in the  early 1980s, colluded to battle agressive legal  environments in numerous nations, but were eventually  taken over by conservative Presbyterians in the late 1980s  due to its superior to their outstanding organization and  numerical dominance. Despite internal disagreement, the  movement's goals of regulating and publicising  homeschooling have been met by the mid-1990s. Since  then, schooling has grown in prominence and is  increasingly being adopted by more mainstream segments  of society, often in conjunction with public schools,  hinting that the term "homeschooling" as a political  organization and ideology may have outlived its use.
Keywords: Education; Families; Homeschooling; Social Movements; Women in Education